Synergistic evolution of dual-precipitation and reverted austenite on mechanical properties in 2.4 GPa ultrahigh strength steel - Aijun Li; Yangxin Wang; Xinyu Jin; Jiaxin Liu; Chundong Hu; Han Dong (Journal of Materials Research and Technology)
Ultrahigh strength steel is of great importance in engineering applications. The experimental steel forms finely dispersed precipitation and a small amount of reverted austenite after cryogenic and aging treatments, endowing it with unique strength and toughness. TEM and APT were employed to characterize the morphology, distribution, and size of the precipitations and reverted austenite in samples after aging at 480–600 °C, while SEM was used to analyze the fracture morphology of tensile specimens subjected to different aging temperatures. The size of the precipitation increases and more reverted austenite is generated as the aging temperature increases. The synergistic effect of the precipitations and reverted austenite enables the steel to achieve an optional balance of strength and toughness at around 510 °C. As the aging temperature gradually increases, precipitation growth reduces their strengthening effect, while the increased spacing between the precipitations enhances toughness. Additionally, the increasing amount of reverted austenite further contributes to improve toughness. The synergistic interaction of these factors results in various mechanical properties of the steel after different heat treatments, providing new theoretical insights for optimizing the performance of ultrahigh strength steel. Furthermore, NiAl not only precipitates uniformly in the matrix of martensite but also facilitates the highly uniform distribution of M2C in the matrix. The growth of reverted austenite at boundaries of martensite reduces the amount of precipitations at the same position. Thus, the synergistic effect of reverted austenite formation at the boundaries and its reduction of precipitations in these positions enhances the mechanical properties of the steel.